Application of Scaffolding Teaching Method in the Course of Introduction to the English-speaking Countries - Wei, Ping; Cui, Ying (Journal of Educational Research and Policies, 2024)
Constructivism is an educational theory which aims at improving students’ creative ability. Scaffolding instruction is the key element of the constructive instruction model and it is a mature teaching method. The course of introduction to the English-speaking countries is a comprehensive course combining the knowledge of the major and the skills, which is to make the students have a general idea of the geography, history, economy, politics and other aspects of the English-speaking countries. The teacher can make use of the Scaffolding instruction to provide the students the studying scaffold. Through the scaffolding instruction, the teacher can help the students finish the construction of knowledge in their future study.